Non invasive monitoring of in-vivo muscle-tendon mechanical properties of athletes with an ultrasonic detection scheme - Hossain, M. Z.; Grill, W. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
A system has been developed and applied for monitoring where the lateral muscle extension is detected with the aid of an ultrasonic caliper. Ultrasonic monitoring is furthermore used to detect synchronously the force exerted by the activated limbs. The resolution for muscle extension is ± 0.01mm and that of force is ± 1.5N. The force-length relation is observed for the gastrocnemius muscle for rising voluntary isometric contraction up to maximum contraction and subsequent relaxation. The measurement principle is based on synchronous monitoring of variations of the time-of-flight of the ultrasound passing the muscle and synchronous monitoring with an ultrasonic force sensor that also serves to keep the flexion of the joint constant. The observed force-length relation displays a hysteresis that is indicative of the athlete's training condition.